IMPLEMENTASI PERMENPAN NOMOR 16 TAHUN 2009 TENTANG JABATAN FUNGSIONAL GURU DAN ANGKA KREDIT (Studi Kasus pada Kenaikan Pangkat dan Dampaknya Bagi Guru SDN di Kecamatan Kandis Kabupaten Siak ) - Reni Reni; Rr. Sri Kartikowati; Nurpit Junus (Jurnal Manajemen Pendidikan Penelitian Kualitatif, 2018)
The objective of this study was to analyze the implementation of ‘Permenpanand Birokrasi’ No. 16/2009 on Teachers’ Functional Position and their credit points and itsimpacts on elementary school teachers’ career development at state elementary schools (SDNs)in Kandis Sub-district, Siak District. The study focused on (1) teachers’ understanding of thecontent of the ministerial decree, (2) the procedures of teacher promotion in accordance withthe ministerial decree, (3) the impacts of the implementation of the ministerial decree on theteacher promotion. The study employed the qualitative approach with descriptive method andthe data were collected using interview, observation and documentation. The interview dataindicated that more than fifty percent of the government employed teachers did not understoodthe contents of the ministerial decree because they were not much kept informed by thegovernment through the department concerned. Half of the remaining respondents did notbother about their promotion. The findings of the research also showed that a small number ofteachers understood the contents of the ministerial decree but they found it difficult to deal withthe promotion process. The Ministerial Decree for Empowerment of National Apparatus andBureaucracy No. 16/2009 has given a positive impact on teachers’ promotion and careerdevelopment and also has given a negative impact on the teachers’ career development in theform of no payment for their professional allowance and the postponement of promotion withinsix years.